Qualitatively speaking: deciding how much data and analysis is enough - Sims, D; Cilliers, F (South African Medical Association, 2023)
As I traverse my (post) doctoral journey, reworking my thesis into publications, I was immersed again in a debate around the utility of the concept of data saturation. I believe this debate to be emblematic of the process of unlearning and relearning that unfolded during my doctoral journey, coming from a biomedical sciences background into qualitative educational research.